Pengaturan Liputan Dan Pemberitaan Televisi Terkait Pidana Anak Dan Implementasinya Oleh KPID Jawa Timur - Adjeng Intan Dewi Prinanti; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
Law Number 32 of 2002 concerning Broadcasting has explained and described the rules regarding broadcast content in the fields of economics, education, religion, race, social and culture properly and correctly. Information technology is currently developing rapidly and of course in future developments information technology will develop even more rapidly. With the development of information technology today, we do not forget the norms that regulate and cannot be separated from Human Rights. The government must guarantee the public's comfort and security in obtaining information by issuing the Broadcasting Law which aims to guarantee the public's security in accessing and obtaining information. Of course, the development of information technology currently has a negative impact on society. However, the existence of the Broadcasting Law is useful for providing guarantees and rights for the public to obtain information in accordance with the regulations that have been regulated